2009
DOI: 10.1098/rspb.2009.0861
|View full text |Cite
|
Sign up to set email alerts
|

Viscous medium promotes cooperation in the pathogenic bacteriumPseudomonas aeruginosa

Abstract: There has been extensive theoretical debate over whether population viscosity (limited dispersal) can favour cooperation. While limited dispersal increases the probability of interactions occurring between relatives, which can favour cooperation, it can also lead to an increase in competition between relatives and this can reduce or completely negate selection for cooperation. Despite much theoretical attention, there is a lack of empirical research investigating these issues. We cultured Pseudomonas aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
237
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 202 publications
(256 citation statements)
references
References 99 publications
(135 reference statements)
15
237
4
Order By: Relevance
“…On the contrary, in this work we have demonstrated that, even if the motility of cooperators and defectors is the same and the spatial domain is homogeneous -so that there are no physical barriers -the natural tendency of cooperators to aggregate into clusters is su cient to preserve cooperation. These findings confirm the results presented in previous theoretical studies by Allison (2005), Durrett and Levin (1994), Fletcher and Doebeli (2009), Hauert and Doebeli (2004), Korolev and Nelson (2011), Nowak and May (1992), Ohtsuki et al (2006), Perc and Szolnoki (2008), Santos and Pacheco (2005), Szabó and Fath (2007) and Taylor et al (2007), and experimental works by Gri n et al (2004), Julou et al (2013), Kümmerli et al (2009) and Momeni et al (2013), and provide further evidence that spatial clustering enhances the benefits of mutual cooperation and plays a crucial role in preserving cooperative behaviours. The spiral structures created by defectors share some striking similarities with spiral waves arising in models of host-parasitoid dynamics, such as those reported by Comins et al (1992), May (1995) and Solé et al (1992).…”
Section: Discussionsupporting
confidence: 81%
“…On the contrary, in this work we have demonstrated that, even if the motility of cooperators and defectors is the same and the spatial domain is homogeneous -so that there are no physical barriers -the natural tendency of cooperators to aggregate into clusters is su cient to preserve cooperation. These findings confirm the results presented in previous theoretical studies by Allison (2005), Durrett and Levin (1994), Fletcher and Doebeli (2009), Hauert and Doebeli (2004), Korolev and Nelson (2011), Nowak and May (1992), Ohtsuki et al (2006), Perc and Szolnoki (2008), Santos and Pacheco (2005), Szabó and Fath (2007) and Taylor et al (2007), and experimental works by Gri n et al (2004), Julou et al (2013), Kümmerli et al (2009) and Momeni et al (2013), and provide further evidence that spatial clustering enhances the benefits of mutual cooperation and plays a crucial role in preserving cooperative behaviours. The spiral structures created by defectors share some striking similarities with spiral waves arising in models of host-parasitoid dynamics, such as those reported by Comins et al (1992), May (1995) and Solé et al (1992).…”
Section: Discussionsupporting
confidence: 81%
“…In both types of competition assays, costs of suicide should manifest in E. coli HK97 outcompeting E. coli l. Finally, we manipulated relatedness at the altruistic trait by competing E. coli l against E. coli HK97 in medium containing different amounts of agarose. Bacterial dispersal is limited in more solid medium [15,16], which increases relatedness among interacting individuals (i.e. Rex-carriers interact more often among themselves than expected based on their relative frequency in the population).…”
Section: Introductionmentioning
confidence: 99%
“…Another plausible mechanism of assortative group formation is population viscosity often via limited dispersal [58,59,[74][75][76]]. Wright's island model [77] and its variants are typical ones in population genetics [30,44,45,78,79], and others prefer network formulations [80][81][82].…”
Section: Resultsmentioning
confidence: 99%
“…An essential feature is that those microbes often clonally reproduce and therefore they are inevitably genetically highly related to each other. The reason for such an assortment is mainly due to spatial structure and limited dispersal [58,59]. As another instance, in larger animals such as primates, we often find nepotistic cooperation among kin [60][61][62].…”
Section: Introductionmentioning
confidence: 99%